Real estate a living autobiography - Levy, Deborah 1959- (Bloomsbury Publishing, 2021)
"Virginia Woolf wrote that in order to be a writer, a woman needs a room of one's own. Now, in [this book], acclaimed author Deborah Levy concludes her ground-breaking trilogy of living autobiographies with an exhilarating, boldly intimate meditation on home and the specters that haunt it. In this vibrant memoir, Levy employs her characteristic indelible writing, sharp wit, and acute insights to craft a searing examination of womanhood and ownership. Her inventory of possessions, real and imagined, pushes readers to question our cultural understanding of belonging and belongings and to consider the value of a woman's intellectual and personal life. Blending personal history, gender politics, philosophy, and literary theory, [this book] is a brilliant, compulsively readable narrative"
"First published in 2021 in Great Britain by Penguin Random House UK"--Title page verso
Keywords: Levy, Deborah -- 1959-; Levy, Deborah; Women authors, English / 20th century / Biography; Women / Social conditions; Feminism; Women authors, English; 1900-1999; Autobiographies; Autobiografie